Pengelolaan Sampah di Sepanjang Sempadan Sungai Kelurahan Pancor dan Kelurahan Sekarteja - M. Akhirudin Nurul Huda; Hasrul Hadi; Armin Subhani (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
This study aims to determine the description of waste management along the river border of Pancor and Sekarteja villages. Determination of data sources is done by purposive sampling, which is chosen with specific considerations and objectives, for example, to people who are considered important and know about problems and waste management. Data collection techniques carried out by observation, in-depth interviews, and documentation. The data collected in this study were analyzed with a qualitative descriptive approach. Furthermore, to test the level of validity of the data carried out by cross-checking (triangulation) especially source triangulation and technical triangulation. Based on the results of the study it can be concluded that the description of waste management along the river border is carried out with seven stages, namely: 1) the presence of garbage generation; 2) worship; 3) direct waste disposal into rivers, vacant land and stove fires; 4) collection; 5) burning rubbish in the yard or on the roadside; 6) the process of transportation by officers to the final disposal site and 7) the final processing (controlled landfill). Thus it can be seen that the community only collects waste around their neighborhoods such as vacant land, as well as several points around the river border. In addition, there are also those who collect it at a temporary landfill which is then transported again to the landfill.